Luteal Phase in Assisted Reproductive Technology - Tesarik, Jan; Conde-López, Cristina; Galán-Lázaro, Maribel; Mendoza-Tesarik, Raquel (Frontiers in Reproductive Health, 2020)
Luteal phase (LP) is the period of time beginning short after ovulation, and ending either with luteolysis, short before menstrual bleeding, or with the establishemnt of pregnancy. During the LP, the corpus luteum (CL) secretes progesterone, and some other hormones, which is essential to prepare the uterus for implantation and further development of the embryo, the function known as uterine receptivity. LP deficiency (LPD) can occur when the secretory activity of the CL is deficient, but also in cases of normal CL function, where it is caused by a defective endometrial response to normal levels of progesterone. LPD is particularly frequent in treatments using assisted reproduction technology (ART). Controlled ovarian stimulation usually aims to obtain the highest number possible of good-quality oocytes and requires the use of gonadotropin-releasing hormone (GnRH) analogues to prevent premature ovulation, and an ovulation trigger to achieve timed final oocyte maturation. Altogether, these treatments suppress pituitary secretion of luteinizing hormone (LH), required for the formation and early activity of CL. In addition to problems of endometrial receptivity for embryos, LPD also leads to dysfunction of the local uterine immune system, with an increased risk of embryo rejection, abnormally high uterine contractility, and restriction of uterine blood flow. There are two alternatives of LPD prevention: a direct administration of exogenous progesterone to restore the physiological progesterone serum concentration independently of the CL function, on the one hand, and treatments aimed to stimulate the CL activity so as to increase endogenous progesterone production, on the other hand. In case of pregnancy, some kind of LP support is often needed until the occurrence of luteoplacental shift. If LPD is caused by defective response of endometrium and uterine immune cells to normal concentrations of progesterone, a still poorly defined condition, symptomatic treatments are the only available solution currently available.